Fatigue failure mechanisms for AlSi10Mg manufactured by L-PBF under axial and torsional loads: The role of defects and residual stresses. (September 2022) - Sausto, F.; Carrion, P.E.; Shamsaei, N.; Beretta, S.
Abstract: Additive Manufacturing (AM) is with no doubt the most revolutionary manufacturing process developed in the last two decades. Despite the indisputable advantages of this technology, the poor surface quality of net-shape components, the presence of internal defects and the development of process induced residual stresses still represent the main problems for the fatigue strength of critical stressed components. In previous works investigating the same alloy, the uniaxial fatigue strength of both machined and net-shape specimens was correlated with the defect size through a Kitagawa diagram, allowing to describe the problem from the threshold perspective. The aim of this work is to extend this approach by investigating the failure mechanisms under torsion in presence of manufacturing defects, both volumetric and superficial anomalies. Specimens manufactured with laser powder bed fusion (L-PBF) technique out of AlSi10Mg, featuring both machined and net-shape surface state, were tested and analysed. The two experimental campaigns allow to investigate the competition between internal defects and superficial features and their effect on the fatigue performances. Tests were performed under two loading conditions, namely fully reverse torsion ( R T = − 1 ) and positive torque ratio ( R T = 0 . 1 ). It was found that for the net-shape specimens manufacturing residual stresses have a key role in influencing fatigue strength of this material, making the fatigue limit in torsion of the two considered loading conditions comparable. All the tested specimens failed onto a maximum principal stress plane, which is in line with multiaxial tests performed on a cast A356-T6 aluminium alloy. In some relatively high shear stresses there is a competition between Mode I and Mode II crack propagation, whose threshold condition is controlled by Δ K th, I . Highlights: Torsional failure mechanisms of additively manufactured AlSi10Mg are investigated. Effects of machined and net-shape surface conditions are taken into account. Residual stresses are measured and their effect on the fatigue is analysed. Two failure mechanisms are identified irrespective of the surface condition. A fracture mechanics approach is used to correlate fatigue results.